Gender Attitudes, Gendered Partisanship: Feminism and Support for Sarah Palin and Hillary Clinton among Party Activists. (1st October 2016) - Sharrow, Elizabeth A.; Strolovitch, Dara Z.; Heaney, Michael T.; Masket, Seth E.; Miller, Joanne M.
ABSTRACT: Activists in the Democratic and Republican parties have distinct concerns about women's place in American politics and society. These views lead them to evaluate female candidates through different ideological lenses that are conditioned, in part, on their divergent attitudes about gender. We explore the implications of these diverging lenses through an examination of the 2008 candidacies of Hillary Clinton and Sarah Palin, using data from an original survey of Democratic and Republican National Convention delegates. We find that delegate sex did not affect their evaluations but that evaluations were influenced by the interaction of partisanship and attitudes about women's roles.